Echocardiographic findings in arterial hypertension, Arzobispo Loayza Hospital, Lima, Peru - Villanueva Muñoz, Omar Ludwing (2010)
Objectives: Determine the echocardiographics findings in patients with arterial hypertension. Methods: Prospective, observational and cross-sectional study. It was calculated a value of 81.6 subjects. 107 patients get into the studio; these patients were treated in outpatient service of Cardiology from the Arzobispo Loayza Hospital (Since April 10th to May 10th, 2010). Results: 72 (67.3%) women and 35(32.7%) men were considering in the studio. Average age was 68.26 ±10.2 years. The Geometry of the LV and Díastolic Dysfunction were analized vs. the blood pressure control and the sex of the patient. The GLV vs. DD, were compared too. Conclusions: There is a higher prevalence of CH in men, and of CR and EH in women. The DD tipe-I had a higher prevalence in patients with CR and CH. The findings were not statistically significant. The relationship among bad BP control, altered left ventricular geometry and DD showed no statistical value.